2020
DOI: 10.1007/s00253-020-10604-0
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring yeast fermentations by nonlinear infrared technology and chemometrics—understanding process correlations and indirect predictions

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…Decoupling such correlations during the calibration (or training) of such models is crucial to reach reliable predictions even when the dynamics of the fermentation change. A common and efficient approach consists of taking samples at different times during the fermentation, and spiking them with different amounts of the analytes of interest to attain partially uncorrelated samples [114] ( Fig. 11e-h).…”
Section: Open-loop Data-driven Monitoring Of Cellulose To Ethanol Fermentioning
confidence: 99%
“…Decoupling such correlations during the calibration (or training) of such models is crucial to reach reliable predictions even when the dynamics of the fermentation change. A common and efficient approach consists of taking samples at different times during the fermentation, and spiking them with different amounts of the analytes of interest to attain partially uncorrelated samples [114] ( Fig. 11e-h).…”
Section: Open-loop Data-driven Monitoring Of Cellulose To Ethanol Fermentioning
confidence: 99%
“…The PLS regression model for glucose was calibrated by creating a set of synthetic samples that contained the fermentation matrix and uncorrelated concentrations of glucose, xylose, and ethanol. 22,23 Xylose and ethanol were also taken into consideration within the calibration due to the overlap of their spectra with glucose, and due to the fact that their dynamic profiles are correlated during the fermentation. Not including them as uncorrelated variables in the calibration samples would result in interference of xylose and ethanol with the prediction of glucose.…”
Section: Pls Calibrationmentioning
confidence: 99%
“…Free-floating wireless sensors are a quite novel and bold sensing technology, based upon non-invasive instrumented particles [45], which can provide access to process data in a harsh environment inside an agitated bioreactor [46] Another recent development is the use of advanced image analysis for process monitoring. For example, current studies have demonstrated that imaging and advanced image analysis, coupled with chemometrics and state-of-the-art machine learning algorithms, are promising to monitor fermentation [47].…”
Section: Pat Solutions and Robotics For Better Controlmentioning
confidence: 99%